В бой идут одни пацаны: [роман] / Александр Тамоников - Тамоников Александр Александрович (Тамоников, 2015)
Экземпляры: (20151015) / Инвентарный номер: 48818 / Цена: 266.00 / Сис.шифр: 84(2Pос=Рус)6 / Авт.знак: Т 17 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6-44